2020
DOI: 10.1002/solr.202000425
|View full text |Cite
|
Sign up to set email alerts
|

Selenium‐Based Solar Cell with Conjugated Polymers as Both Electron and Hole Transport Layers to Realize High Water Tolerance as well as Good Long‐Term and Thermal Stability

Abstract: Solar cells with varied absorbers, ranging from crystalline silicon to perovskite materials, are very vulnerable to water. Expensive and complicated encapsulation is needed to protect the devices. Thus, it is highly desirable to achieve encapsulation‐free solar cells with high water tolerance. Herein, encapsulation‐free selenium (Se)‐based solar cells (SSCs) with hydrophobic polymers as electron and hole transport layers are presented and can successfully tolerate the aqueous conditions. Moreover, it is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…[17,18] Further studies have demonstrated encapsulationfree tolerance toward aqueous conditions by use of hydrophobic polymer transport layers. [19] In this study, we report the first bifacial selenium solar cell with a state-of-the-art performance above 5% PCE from frontside illumination (through the n-type contact) and 2.7% PCE from back-side illumination (through the p-type contact) for devices with contact areas above 0.4 cm 2 . For these contact area sizes, we show better bifacial cell performance than any reported monofacial cells of similar size.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[17,18] Further studies have demonstrated encapsulationfree tolerance toward aqueous conditions by use of hydrophobic polymer transport layers. [19] In this study, we report the first bifacial selenium solar cell with a state-of-the-art performance above 5% PCE from frontside illumination (through the n-type contact) and 2.7% PCE from back-side illumination (through the p-type contact) for devices with contact areas above 0.4 cm 2 . For these contact area sizes, we show better bifacial cell performance than any reported monofacial cells of similar size.…”
Section: Introductionmentioning
confidence: 90%
“…[ 17,18 ] Further studies have demonstrated encapsulation‐free tolerance toward aqueous conditions by use of hydrophobic polymer transport layers. [ 19 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 , 5 ] Amorphous Se (a‐Se) stands as the currently market‐dominant photoconductive material in X‐ray imaging industry, particularly in X‐ray flat‐panel detectors for digital mammography. [ 6 , 7 ] Crystalline Se (c‐Se) is regaining significant attention as a promising absorber for top cells in multi‐junction solar cells and indoor photovoltaics (IPVs) due to its suitable wide bandgap of ≈ 1.9 eV, [ 8 , 9 , 10 , 11 , 12 , 13 ] excellent intrinsic phase and environmental stability to ambient conditions such as humidity, light and oxygen, [ 14 , 15 , 16 ] and nontoxicity as an essential element for humans. [ 17 , 18 , 19 ] In addition, the high piezoelectricity, thermoelectricity, and nonlinear optical responses of Se have also propelled its widespread use in various applications including wearable piezoelectric devices, thermoelectric devices, optical limiters, and field‐effect transistors.…”
Section: Introductionmentioning
confidence: 99%